2007
DOI: 10.1212/01.wnl.0000248190.45078.e6
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Kernohan notch

Abstract: Abstract-Objective:To investigate the association of an indicator of hippocampal function with severity of depression symptoms in temporal lobe epilepsy. Methods: We evaluated 31 patients with video/EEG-confirmed temporal lobe epilepsy using creatine/N-acetylaspartate ratio maps derived from a previously validated 1 H magnetic resonance spectroscopic imaging ( 1 H-MRSI) technique at 4.1 T. We also assessed depression symptoms, epilepsy-related factors, and self-perceived social and vocational disability. We us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Last, it presented hypointense signal in gradient echo sequence [ 5 ] and evidence of blood-brain barrier rupture in post-contrast T1-weighted imaging [ 21 ]. Middle-term and long-term aspect displayed hypointense signal in T1-weighted sequence [ 27 ], and hyperintense signal in T2-weighted [ 8 , 15 , 27 , 44 ] and FLAIR imaging [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Last, it presented hypointense signal in gradient echo sequence [ 5 ] and evidence of blood-brain barrier rupture in post-contrast T1-weighted imaging [ 21 ]. Middle-term and long-term aspect displayed hypointense signal in T1-weighted sequence [ 27 ], and hyperintense signal in T2-weighted [ 8 , 15 , 27 , 44 ] and FLAIR imaging [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The medium-term and long-term aspect of the midbrain lesion associated with KWNP displayed the neuroimaging features of “white matter hyperintensity (WMH)” [ 18 ] which corresponds to hyperintensity in T2 [ 8 , 15 , 27 , 44 ] and FLAIR sequence [ 44 ] after ischemic stroke. Hypointensity in T1-weighted imaging indicated cerebral atrophy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although FTLD phenotypes such as these share some clinical features with Alzheimer's disease (AD), research suggests that other behavioral and cognitive characteristics distinguish FTLD phenotypes from each other and from AD. 6,7 Previous neuropsychological studies 6,8 have focused on the cross-sectional distinctions between FTLD and AD and this research has augmented our understanding of the pathology and diagnoses of these dementia syndromes. By contrast, there has been much less research comparing and contrasting the longitudinal decline in AD and FTLD.…”
Section: Introductionmentioning
confidence: 99%
“…Signal changes were seen even when MRI was performed 9 months after injury [ 14 ]. Oster et al [ 15 ] reported that the T2 hyperintense lesion on a KWNP patient can resolve with rehabilitation. Moon et al [ 16 ] described that a lack of MRI signal change may correlate with a better functional prognosis.…”
Section: Discussionmentioning
confidence: 99%